Entre lutas, porongas e letras: a escola vai ao seringal (re) colocações do Projeto seringueiro (Xapuri/Acre 1981/1990) - Jose Dourado de Souza (2011)
This study examined an educational experience with seringueiros (rubber tappers) in the region of Xapuri / Acre, part of the South-West Amazonia, entitled Projeto Seringueiro (Rubber Tappers Project). The experience, conceived from a perspective of popular education, influenced by the ideas and practices of Paulo Freire, Liberation Theology and by a Brazilian rural syndicalism, associated with the Nacional dos Trabalhadores na Agricultura - CONTAG (National Confederation of Agricultural Workers) in Acre, integrated the Social, Environmental and of Struggle for Land Movement. The objective of this study was to analyze the circumstances and socio-historical contexts of the emergence and implementation of that educational project - that was erected inside of the Projeto Seringueiro - focusing on their first period elapsed between 1981 and 1990. It also explored some of the general elements of its structure and functioning, besides its origins and consolidation. It presented and still described mainly the social actors, individuals and collectives involved in the educational proposal, indicating some of its protagonists, their relationships, similarities and differences in this early period, when through the Projeto Seringueiro, the school reached the seringais (rubber settlements) and other placements. The theoretical and methodological base of this research is guided by a socio-historical contribution, within the framework of the English Social History, especially the thought of Edward P. Thompson. In this regard, the analyses stressed that working in the field of history should consider the interrelationship between the dimensions and contradictions of reality in its processes and dynamics, and that the confrontation between social being and social consciousness gives rise to new problems and leads to the experience. Based on documentary analysis, the research methodology was conducted by the survey and study of archival documents mainly from the Centro dos Trabalhadores da Amazônia - CTA (Center for Amazonian Workers). The survey findings suggest a process riddled with continuities and discontinuities, quests and conquests, as a result of the protagonists actions, in which the ability to learn to read, write and count was being appropriated by them. As the poronga (lamp) lightened the roads of the seringal, the school through the school handbook, cleared the ideas, according to their students/seringueiros. In this road, it was necessary to understand the reasons which took an education project to a seringal. In short, the research was oriented by a concept that seeks to discover the elements and dynamics of the processes constructed by the action of social actors, having regard to collective action and the dynamics of transformative praxis of men as historical actors.